2016
DOI: 10.1177/2325967116669490
|View full text |Cite
|
Sign up to set email alerts
|

Are the Current Classifications and Radiographic Measurements for Trochlear Dysplasia Appropriate in the Skeletally Immature Patient?

Abstract: Background:The assessment and classification of trochlear dysplasia in pediatric patients has yet to be well documented or validated.Purpose:To examine several different measurements/classifications of trochlear dysplasia in skeletally immature patients to assess inter- and intraobserver reliability and to determine which best correlates with patellar instability.Study Design:Cohort study (diagnosis); Level of evidence, 3.Methods:Radiographs and magnetic resonance imaging (MRI) scans of 36 skeletally immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 20 publications
2
49
2
Order By: Relevance
“…[7][8][9][10]12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] These included five publications that compared between TT-TG distances measured using CT and MRI, [7][8][9][10]12 and 21 publications that compared between TT-TG distances for patients with and without patellofemoral instability. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Collectively, these included a total of 3,040 patients. The details of the study design and patient population of all the studies are reported in ►Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10]12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] These included five publications that compared between TT-TG distances measured using CT and MRI, [7][8][9][10]12 and 21 publications that compared between TT-TG distances for patients with and without patellofemoral instability. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Collectively, these included a total of 3,040 patients. The details of the study design and patient population of all the studies are reported in ►Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…4). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Pooling of all the patients from these 18 studies then revealed that the mean TT-TG distance for the control group was 12.85 mm (95% CI: 11.71-14.01), while the mean TT-TG distance for patients with patellofemoral instability was 18.33 mm (95% CI: 17.04-19.62) when measured on CT. When measured on MRI, the mean TT-TG distance for the control group was 9.83 (95% CI: 9.11-10.54) while the mean TT-TG distance for patients with patellofemoral instability was 15.33 (95% CI: 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the dysplastic patellofemoral joint can be reliably evaluated in the skeletally immature patient population, particularly in terms of evaluating chondral surfaces. 32 A total of 65 patients met the inclusion criteria for this study. The average age of included patients was 14.2 years (range, 9.2-18.1 years), and the sex distribution was nearly even (54% male, 46% female).…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, a control group was not included. Given the difficulty in obtaining adequate films and the variable interpretation of these images, the use of the four-grade Dejour classification to evaluate trochlear dysplasia can also be considered a limitation of this study [52,53]. We have tried our best to obtain adequate films and maybe we can use CT or MRI to evaluate trochlear dysplasia in later studies.…”
Section: Discussionmentioning
confidence: 99%